2009
DOI: 10.1007/s00468-009-0351-y
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis studies on European evergreen and deciduous oaks grown under Central European climate conditions: II. Photoinhibitory and light-independent violaxanthin deepoxidation and downregulation of photosystem II in evergreen, winter-acclimated European Quercus taxa

Abstract: In the context of the search for future forestry species in Central Europe under climate change scenarios, the evergreen Mediterranean Quercus taxa Q. ilex ssp. ilex and Q. suber and the semideciduous hybrids. Q. 9 turneri and Q. 9 hispanica were studied in relation to their photochemical efficiency of photosystem II and to the activity of the xanthophyll cycle under Central European winter conditions. The evergreen taxa were remarkably insensitive to winter stress in the field and reacted towards frost period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Recently, Peguero-Pina et al (2009) showed that only Q. ilex and not Q. suber uses high predawn DES as a photoprotective mechanism under summer drought conditions. Our data of short-term frost effects (Brüggemann et al 2009) and the present field study indicate that Q. suber, however, may well use high morning DES as a photoprotective mechanism under winter frost stress conditions, and it inherits this trait to the hybrid, Q. × hispanica.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Recently, Peguero-Pina et al (2009) showed that only Q. ilex and not Q. suber uses high predawn DES as a photoprotective mechanism under summer drought conditions. Our data of short-term frost effects (Brüggemann et al 2009) and the present field study indicate that Q. suber, however, may well use high morning DES as a photoprotective mechanism under winter frost stress conditions, and it inherits this trait to the hybrid, Q. × hispanica.…”
Section: Discussionmentioning
confidence: 55%
“…3E,F) or the two processes are not coupled at this stage of winter acclimation. It has been shown earlier that in winter-acclimated evergreen Quercus and other sclerophyllous species F v /F m and DES often are (Verhoeven et al 1999, Brüggemann et al 2009), but need not always be (Fig. 3 in Martinez-Ferri et al 2004) coupled to each other.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…We here present evidence that such intermittent decreases of photosynthetic activity during winter are not necessarily just a result of changing weather conditions influencing the measurements in situ, but may well reflect either reversible ''damage'' of the photosynthetic apparatus by ''dynamic'' photoinhibition or down-regulation of PS II by ''chronic'' photoinhibition (Adams et al 2004). Evidence for this interpretation has been found in an adjacent survey (Brüggemann et al 2009). It can, however, not be ruled out, that low, especially sub-freezing temperatures, may also have affected other cellular components such as membrane integrity or enzymatic activity of Calvin cycle enzymes.…”
Section: Discussionmentioning
confidence: 69%